EFEKTIFITAS PROGRAM AUSTRALIA-INDONESIA PARTNERSHIP FOR DECENTRALIZATION DALAM MENINGKATKAN KAPASITAS PERENCANAAN DAN PENGANGGARAN DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN SITUBONDO TAHUN 2012 - F.A., Vury Ayunindya (Fakultas Ilmu Sosial dan Ilmu Politik, 2014)
There are many things affecting the approval of a budgeting draft. However, one thing predominantly related is its relationship with the executive as the equal partner. Executive and legislative as the local government organizers have diverse political interests. Given the executive and legislative is similarly through political process called the election. Therefore, the coordination between the executive and the legislature in drafting documents related to the planning and budgeting is disturbed, then it affects on the unpunctuality of the budgeting draft endorsement.The problem has triggered AIPD, as a donor institution with special emphasis on decentralization in Indonesia, to deal with the existing problems. The AIPD effort to help the parliament is by building partnerships between AIPD and the Parliament. The partnership program is realized through the provision of a number of trainings aimed to enhance the capacity of Parliament in planning and budgeting.This study uses Capacity Building and Effectiveness Theory. This research is conducted at the Parliament of Situbondo Regency on period of 2009-2014. The type of this research is descriptive qualitative research. Data collection techniques used are interviews and documentation. Selection of informants uses purposive sampling technique.The analysis shows that the process of the parliament capacity building in planning and budgeting given by AIPD can enhance the capacity of members of the Parliament in planning and budgeting. The increase of capacity has created a punctuality of the Parliament members of Situbondo at the period of 2009-2014 in legitimating the budgeting draft for the subsequent years.According to the results of the research, program of the Parliament capacity building in planning and budgeting is considered effective. Therefore, the programs that have positive impact on the development of Situbondo Regency, mainly for the Parliament of Situbondo at 2009-2014 period is expected to implement a sustainable partnership.Keywords: partnership, capacity building